2012
DOI: 10.1155/2012/815308
|View full text |Cite
|
Sign up to set email alerts
|

The Treg/Th17 Imbalance in Patients with Obstructive Sleep Apnoea Syndrome

Abstract: Obstructive sleep apnoea syndrome (OSAS) is a chronic inflammatory disease regulated by T lymphocytes. Our purpose is to assess the pattern of Th17 cells and CD4+CD25+Foxp3+ regulatory T (Treg) cells in peripheral blood of patients with OSAS. Fourty-four OSAS men and 20 healthy volunteers were enrolled. Twenty-three patients were classified into mild to moderate group and 21 cases were classified into severe group according to the severity of OSAS. We detected the frequencies of Th17 and Treg and related serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
3
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 35 publications
3
45
3
3
Order By: Relevance
“…The identification of Th 17 and T reg cells progressed understanding of the mechanisms underlying immune dysfunction. An imbalance of Th 17 /T reg cells has been widely detected in human cancer, inflammatory and autoimmune diseases (9); however, to the best of our knowledge, it has yet to be associated with thoracotomy in patients with lung cancer.…”
Section: Introductionmentioning
confidence: 98%
“…The identification of Th 17 and T reg cells progressed understanding of the mechanisms underlying immune dysfunction. An imbalance of Th 17 /T reg cells has been widely detected in human cancer, inflammatory and autoimmune diseases (9); however, to the best of our knowledge, it has yet to be associated with thoracotomy in patients with lung cancer.…”
Section: Introductionmentioning
confidence: 98%
“…Numerous studies have demonstrated elevated levels of circulating proinflammatory cytokines, chemokines, and adhesion molecules in patients with OSA in comparison with those in matched control patients. 4,[9][10][11]26,27 In particular, the potent proinflammatory cytokine TNF-α has been evaluated by several case-control studies that have consistently shown elevated levels in patients with OSA compared with those in control patients. 4,9-11 TNF-α is the most influential inflammatory cytokine in the pathogenesis of RA, and the effectiveness of anti-TNF-α therapy has been demonstrated in RA.…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated a positive correlation of peripheral Th17/Treg ratio with the incidence of apnea/hypopnea index (AHI) in OSAS adults (6). HIF-1 is proved as a check point of Th17/Treg polarization (7).…”
mentioning
confidence: 86%
“…PSG was conducted using the Embla-Monet 32 Sleep System (Embla, Broomfield, CO) and manually scored by a single registered technologist as described in our previous work (6,27,28). Hypopnea was defined as a decrease of ≥30% in thoracoabdominal motion associated with a fall in baseline oxygen saturation of >4%.…”
Section: Overnight Polysomnographymentioning
confidence: 99%